PENGARUH LATIHAN VARIASI TIANG RINTANG TERHADAP KETERAMPILAN SHOOTING DALAM PERMAINAN FUTSAL PADA MAHASISWA UNIVERSITAS MEGAREZKY - Suhardianto, Suhardianto; Ismail, Agus (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2019)
This research aimed to know whether there is an effect of the variation training in the obstacle column to the accuracy of shooting skills in futsal games for students of Megarezky University. This research was experimental research that used Pre-experimental design (nondesigns) with one group pretest and posttest design. The population was male futsal athlete of Megarezky University which consisted of 25 students. The Retrieval of data used research instruments by giving an initial test (pretest). Then treated with a target game (treatment), after that the final test was given (posttest). The sampling technique was done by sampling technique saturated (total sampling). The data analysis technique used normality, homogeneity and t-test. at a significant level of 5%. The result of research showed that there was an influence of the variation of the obstacle column to the shooting accuracy skill, which is obtained t-count of 2.559> t-table of 2.059 while the significant value of 0.012 <? 0.05. Because the significant level was smaller than ? 0.05, there was a significant effect of data on the pretest and posttest shooting skills in the futsal game for students of Megarezky University. This is evidenced from the average posttest value greater than the pretest value or (21.08: 25.28) with the difference (4.20). Thus it was concluded that there was a significant influence of obstetric vasriation practice on Shooting skills in the futsal game for Students of Megarezky University .